Dun Arnistean (Scottish Historical and Archaeological Internet Reports, 2009)
This chapter present details of physical description, location, extent of erosion, method of access and previous work. The site is of great interest and importance to the settlement record of Ness. The fact that it has been examined in some detail by many others over the past 40 years adds historical significance to the site. The recovery of large amounts of material demonstrated that there are archaeological remains still worthy of investigation on the site. It seems likely that a late Iron Age/Norse building is present.